CHILDREN'S RESPIRATORY DISEASE, SCHOOLS AND DAY-CARE CENTERS (Tufts Archival Research Center, 2007)
Draft; Draft of a report regarding the increase in asthma and other respiratory illnesses in children and adults. Cites poor indoor air quality (IAQ) as the possible cause for this. Disregards the notion that secondhand smoke is a major contributor due to the fact that the number of people who smoke has been decreasing in recent years and children spend more time outside the home than in it, due in part to the increase in day care facilities.